AB1070 Comparison of Ultrasound Disease Activity Score in Assessing Joint Inflammation in RA: Comparison with CDAI. (9th June 2015) - Oliveira, M.A.; Machado, A.; Monteiro, P.; Cunha, I.; Mugeiro, M.J.
Abstract : Background: Various clinical composite scores have been developed to assess disease activity and follow-up in patients with rheumatoid arthritis (RA). Ultrasound (US) examination can be a valuable help in clinical evaluation and in monitoring evolution of these patients. It is desirable to have a representative US composite score, in which most representative joints are included, that reflect a patient's overall disease activity. Objectives: To evaluate the correlation between Disease Activity Score of 28 joints (DAS-28), Clinical Disease Activity Index (CDAI) and Simplified Disease Activity Index (SDAI), with ultrasound findings in both Gray-scale (GS) and Color Doppler (CD). To compare a Clinical disease activity index (CDAI) with an ultrasound-based composite disease activity index (sCDAI). Methods: Thirty nine patients with RA were selected from database of a rheumatology unit according to age, sex and treatment by a blinded observer to the clinical activity and duration of disease. Patients underwent clinical evaluation by two different observers. Laboratory data, DAS 28, CDAI and SDAI were collected. Two different experienced sonographers blinded to clinical and demographic data, performed US evaluation in GS and CD of twelve joints (bilaterally: wrists, second, third and fifth metacarpophalangeal joints and second and fifth proximal interphalangeal joints). Synovitis was scored in GS and CD in a semi-quantitative way from 0 to 3. Spearmen's correlation coefficients were calculated to determine correlations between composite disease activity indices (DAS 28, SDAI, CDAI) and sonographic findings. A sonographic CDAI (sCDAI) was calculated. To calculate this index we replace the results of the twelve joints evaluated by US instead of using the results of the clinical examination of these same SJ in the CDAI. Results: DAS-28, CDAI and SDAI have a statistically significant correlation with both GS≥1 and CD ≥1 US findings. The correlation between DAS 28 and GSUS and CDUS was 0, 38 (p=0, 018) and 0, 40 (p=0, 012). The correlation between CDAI and GSUS and CDUS was 0, 41 (p=0, 01) and 0, 58 (p≤0, 001). The correlation between CDAI and GSUS and CDUS was 0, 35 (p=0, 027) and 0, 49 (p=0, 001). The average of the results of the CDAI (10, 849±8, 69) evaluation were very similar to the results obtained with sCDAI (10, 83±8, 89), when we use the presence of both GS and CD ≥1 to define synovitis. The results of the CDAI and sCDAI were not in agreement when to definite synovitis by US we use the results of GSUS or CDUS (14, 67±9, 05). Conclusions: There is a good correlation between the results of clinical examination appreciated by DAS 28, CDAI and SDAI and the US findings. The results of the sonography CDAI (sCDAI) were very similar to the CDAI, when we use both GS and CD US data to definite synovitis. However, when we only use GS data to define synovitis, sCDAI have a higher mean result.This is a very initial study that is trying to find the optimal number of joints to be evaluated by US in clinical practice. References: Damjanov N et al. Construct validity and reliability of ultrasound disease activity score in assessing joint inflammation in RA: comaprison with DAS-28. Rheumatology 2012; 51:120-128. Gärtner M et al. Sonographic joint assessment in rheumatoid arthritis. Arthritis and Rheum 2013, Vol 65 (8): 2005-2014. Disclosure of Interest: None declared